Climate change and food security in Northern Bangladesh: experience of RDRS in implementing Stress Tolerant rice - Obayed, Joynub Nabila (BARC University, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2017.